An illustrated checklist of Bromeliaceae from Parque Estadual do Rio Preto, Minas Gerais, Brazil, with notes on phytogeography and one new species of Cryptanthus - Versieux, L. M.; Louzada, R. B.; Viana, P. L.; Mota, N.; Wanderley, M. D. L. (Phytotaxa, 2014)
A checklist of the 14 genera and 34 species of Bromeliaceae from the Parque Estadual do Rio Preto in Sao Goncalo do Rio Preto municipality, Minas Gerais state, southeastern Brazil, is presented. The Tillandsioideae was the most diverse subfamily and was found to be concentrated in rocky field areas. Bromelioideae is also a species rich subfamily, but its taxa have shown a preference to forested areas and savannas at lower altitudes. Pitcairnioideae is highlighted by its level of endemism, but has only four species. Cryptanthus micrus, a new species found in this area is described and illustrated. Our cluster analysis indicated that the Rio Preto State Park has a Bromeliaceae flora more similar to that from Pico do Itambe and Grao Mogol State Parks. Taxa like Dyckia glandulosa, Orthophytum itambense and Vriesea medusa, which were previously considered to be endemic to Pico do Itambe, now have their area of occurrence extended to Rio Preto. These new occurrences highlight the importance to create a corridor joining these neighboring reserves to connect populations of narrowly ranged or rare species. In this work we present pictures of 19 species in their habitats within the park, and we hope that these illustrations will help in the identification and conservation of these taxa.